Coupling Resonant Modes of Embedded Dielectric Microspheres in Solution‐Processed Solar Cells. Issue 2 (12th February 2013) - Mihi, Agustín; Bernechea, Maria; Kufer, Dominik; Konstantatos, Gerasimos
<x xml:space="preserve">Abstract</x> Resonant modes of dielectric microspheres are coupled into solution processed solar cells, resulting in an enhancement in photocurrent. Three different locations of the sphere monolayer within the absorbing PbS quantum dot layer are investigated in an attempt to maximize the number of resonant modes leaked into the PbS. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>